2020
DOI: 10.1016/j.yebeh.2019.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and the burden of prolonged seizures in noninstitutionalized children with epilepsy

Abstract: This study aimed to provide information on the burden of illness and health-related quality of life (HRQoL) in children with epilepsy who experience prolonged acute convulsive seizures (PACS) in the community setting, and to investigate factors that may predict poor HRQoL in this population. Methods: Noninstitutionalized children (aged 3-16 years) who had experienced at least one PACS within the past year and had currently prescribed PACS rescue medication were enrolled in a cross-sectional study in Germany, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Improving the interval between seizures improves quality of life not only for the patient but also for the entire family unit, including parents and siblings [22][23][24]. Further, reducing the frequency of prolonged acute convulsive seizures has the potential to improve quality of life by preventing episodes of status epilepticus and associated long-term, irreversible neurological sequelae [25].…”
mentioning
confidence: 99%
“…Improving the interval between seizures improves quality of life not only for the patient but also for the entire family unit, including parents and siblings [22][23][24]. Further, reducing the frequency of prolonged acute convulsive seizures has the potential to improve quality of life by preventing episodes of status epilepticus and associated long-term, irreversible neurological sequelae [25].…”
mentioning
confidence: 99%
“…This instrument can serve as a measurable proxy to improve the clinical pathway in CECTS. At present, this is likely the optimal method to estimate the overall burden of epilepsy 30,31 and ASM therapy on patients and their family.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies on the Indian, [ 10 , 11 ] the Nigerian, [ 12 ] and the European [ 13 ] CWEs reported that epilepsy significantly affected the QoL in children. There are very limited studies conducted on these aspects from the Jiangsu region of China that have shown more focus on this issue.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Health-related quality of life (HRQoL) is a multidimensional concept that includes emotional, mental, physical, behavioral, and social aspects of the well-being and functioning of the patients. [9] Cross-sectional studies on the Indian, [10,11] the Nigerian, [12] and the European [13] CWEs reported that epilepsy significantly affected the QoL in children. There are very limited studies conducted on these aspects from the Jiangsu region of China that have shown more focus on this issue.…”
Section: Introductionmentioning
confidence: 99%